Helicobaceter pylori prevalence in duodenogastrik reflux demostrated by scintigraphic technique in patients with gastric operation - Mehmet CİNDORUK and Tamer ATASEVER and Şükrü DUMLU and Ümit Bilge DOĞAN and Berna OKUDAN and Candan TUNÇER and Mustafa ÜNLÜ and Uğur KANDİLCİ (Turkish Journal of Gastroenterology, 2019)
-